Method for technical and economic evaluation of the effectiveness of reliability improvement of military aircraft gas-turbine engines in their aftersales support based on outcome performance measures - Asadullin, Marsel' Raufovich (Vestnik Permskogo universiteta. Seria Ekonomika = Perm University Herald. Economy; Vol 3 No 30 (2016)DO - 10.17072/1994–9960–2016–3–77–91, 2019)
The article describes a conflict between interests of the state customer and the prime contractor on the issue of aeronautical systems and subsystems reliability improvement during its aftersales support. The conflict between interests is shown to arise under the traditional approach to payment for the prime contractor’s services on a basis called “costs+”. Contractual models of public-and-private partnership which are used in the foreign countries successfully, with a payment scheme for the contractor’s services based on outcome performance measures of aeronautical systems and subsystems aftersales support, are presented as a conflict settlement mechanism. A long validity term of such contracts and independence of performance payment amounts from the contractor’s actual expenses motivate the private partner to hold some activities aiming at systems and subsystems reliability improvement. Applicability of technical and economic assessment of these activities is demonstrated. The main provisions of the method for technical and economic evaluation of the effectiveness of aeronautical systems and subsystems reliability improvement are presented thorough the example of a fleet of engines operated within a group of military transport aircrafts with their aftersales support based on outcome performance measures. The method is based on a simulation model of engines fleet operating which allows for the measures of technical and economic evaluation to be identified: average availability of the military transport aircrafts group during the contract validity period, state customer’s operating costs and the prime contractor’s profit. It is experimentally shown on the developed method basis that when the fleet of engines is supported aftersales based on outcome performance measures the prime contractor has an economic interest to improve engines reliability above the requirements specified in the regulatory documentation. Keywords technical and economic evaluation, simulation modeling, availability of aeronautical systems and subsystems, conflict between interests, aftersales support, outcome performance measures, gas turbine aircraft engine, gas turbine engine reliability, operating time between unscheduled removals, military transport aircraft. References 1. Akimov V. Osnovy nadezhnosti gazoturbinnykh dvigatelei [Fundamentals of reliability of gas turbine engines]. Moscow, Mashinostroenie Publ., 1987. 207 p. 2. Akimov V.M., Starik D.E., Morozov A.A. Ekonomicheskaia effektivnost' povysheniia resursa i nadezhnosti gazoturbinnykh dvigatelei [Cost-effectiveness of increasing life and reliability of gas turbine engines]. Moscow, Mashinostroenie Publ., 1972. 172 p. 3. Aleksandrovskaia L.N., Afana-s'ev A.P., Vlasov A.A. Sovremennye metody obespecheniia bezotkaznosti slozhnykh sistem [Modern methods of ensuring reliability of complex systems]. Moscow, Logos Publ., 2001. 208 p. 4. Asadullin M.R. Metodika opredeleniia optimal'nykh uslovii kontrakta zhiznennogo tsikla (na primere aviatsionnogo dvigatelestroenia) [Methods of determining the optimal contract terms for the life cycle contract (with an example of aircraft engine buiding)]. Kakaia ekonomicheskaya model' nuzhna Rossii? Materialy II Permskogo kongressa uchenykh-ekonomistov, 11 fevr. 2016 [What is the economic model does Russia need? Proceedings of the II Congress of the Perm academic economists, 11 Feb. 2016]. Perm, Perm.gos.nats.issled.un-t Publ, 2016, pp. 126–132. (In Russian). 5. Barzilovich Yu.N. Kazantsev V.G., Savenkov M.V. Nadezhnost' aviatsionnykh sistem [The reliability of aircraft systems]. Moscow, Transport Publ., 1982. 182 p. 6. Beshelev S., Gurvich F. Matematiko-statisticheskie metody ekspertnykh otsenok [Mathematical and statistical methods of expert assessments]. Moscow, Statistika Publ., 1980. 264 p. 7. Voprosy matematicheskoi teorii nadezhnosti. Pod red. B.V. Gnedenko. [Questions of mathematical theory of reliability. Edited by BV Gnedenko]. Moscow, Radio i sviaz' Publ., 1983. 376 p. 8. Klochkov V.V. Organizatsionno-ekonomicheskie osnovy obespecheniia konkurentosposobnosti vysokotekhnologichnykh proizvodstv (na primere aviatsionnogo dvigatelestroeniia). Diss. doct. ekon. nauk [Organizational-economic bases of maintenance of competitiveness of high-tech industries (for example, aircraft engine). Dr. econ. sci. diss.]. Moscow, 2007. 319 p. 9. Mikhailov A.A. Model' ekspluatatsii parka dvigatelei s uchetom ispol'zovaniia strategii upravleniia resursami [Model of the engine operation based on the use of the park management strategies]. Vserossiyskiya nauchno-tekhnicheskaia konferentsiia «Nauchnye chteniia po aviatsii, posviashchennye pamiati N.E. Zhukovskogo». Sbornik tezisov, 2004 [All-Russian Scientific Conference "Scientific Readings on aviation, dedicated to the memory of NE Zhukovsky". Abstracts.]. Moscow, VVIA im. prof. N.E. Zhukovskii Publ., 2004. (In Russian). 10. Pozhiznennyy kontrakt [Lifetime contract]. Biulleten' operativnoi informatsii «Moskovskie Torgi» [Operational Information Bulletin “Moscow's bidding”], 2014, no. 11. Available at: http://e-torgi.ru/index.php/stati-2/7691-pozhiznennyj-kontrakt (accessed 03.03.2015). 11. Pisarev V.N. Primeneniye teorii massovogo obsluzhivaniia v zadachakh inzhenerno-aviatsionnogo obespecheniia [Application of queuing theory to problems of engineering and aviation support]. Moscow, VVIA im. N.E. Zhukovskogo Publ., 1965. 44 p. 12. Rumiantsev Ye.A., Osovskii V.P., Protopopov V.A. Inzhenerno-aviatsionnoye obespechenie boevykh deistvii chastei aviatsii vooruzhennykh sil i ekspluatatsiia aviatsionnogo oborudovaniia [Engineering and air support combat operations aviation units of the armed forces and the operation of aircraft equipment]. Moscow, VVIA im. N.E. Zhukovskogo Publ., 1989. 398 p. 13. Smirnov N. Nauchnyye osnovy postroeniia sistemy tekhnicheskogo obsluzhivaniia i remonta samoletov GA [Scientific bases of construction of system maintenance and repair of commercial aircrafts]. Moscow, MSTUCA Publ., 1994. 107 p. 14. Smirnov N.N., Itskovich A.A. Obsluzhivanie i remont aviatsionnoi tekhniki po sostoianiiu [Maintenance and repair of aviation equipment at a technical condition]. Moscow, Transport Publ., 1987. 272 p. 15. Chudaeva A.A. Nadezhnost' i srok sluzhby oborudovaniia kak ekonomicheskaia kategoriia [The reliability and service life of equipment as an economic category]. Vestnik of the Orenburg State University, 2009, no. 8 (102), pp. 150–155. 16. Aguilar M., Estrada G., Myers J. Decision-support quantitative models for valuing incentives in performance-based contracts. Monterey, CA, Naval Postgraduate School Publ., 2005. 112 p. 17. Deloitte Consulting LLP. Performance based logistics in aerospace & defense. A rapidly growing market providing lower overall sustainment costs for military equipment and profitable growth opportunities for defense contractors. Available at: http://www. deloitte.com.br/publicacoes/2007/Performance_Based_Logistics_in_A&D.pdf (accessed 29.12.2014). 18. Guajardo J., Cohen A., Kim S., Netessine S. Impact of performance-based contracting on product reliability: an empirical analysis. Available at: http://faculty.som .yale.edu/sangkim/PBC-Reliability-Empirical.pdf (accessed 03.03.2015). 19. Kim S., Cohen M, Netessine S. Reliability or inventory? Analysis of product support contracts in the defense industry. Available at: http://sites.insead.edu/facultyresear ch/research/doc.cfm?did=47947 (accessed: 14.11.2015). 20. PBC Discussion Paper v1.0. Next generation performance-based support contracts – Achieving the Outcomes that Defence Requires. Available at: http://www.defence.gov.au/dmo/ Multimedia/Next_GPBSC-9-5978.pdf (accessed 15.03.2015). 21. Randall W., Nowicki D., Hawkins T. Explaining the effectiveness of performance-based logistics: a quantitative examination. The International Journal of Logistics Management, 2011, vol. 22, issue 3, pp. 324–348. doi: http://dx.doi.org/10.1108/09574091111181354. 22. Sopranos K. Performance-based logistics helps Boeing boost mission readiness. Available at: http://www.boeing.com/news/fronti ers/archive/2007/august/i_ids01.pdf (accessed 30.03.2015).